(untitled) (E Conference Zone, 2022)
This article provides examples of how important metaphorical terms are not only in the field of literature and art, but also in other fields, that is, in the field of medicine. In the sense that the term "health" is used in communication between patients and doctors in medicine, and due to the fact that many advances in this field, metaphorical terms are used in the culture of each language and even in everyday communication in each field. The ideas are approved with examples and provides a wider conceptualization of the problem